Growth rate of rex, satin rabbits and their cross fed with lactosym@ in an intensive raising system - Djamura Aritonang; N.A Tul Roefiah; Tiurma Pasaribu; Yono C Raharjo (Jurnal Ilmu Ternak dan Veteriner, 2003)
An experiment was conducted to study the effect of breed, level of lactosym and their interaction on the growth performance of three breeds of rabbit, i.e.: Rex, Satin and their Cross. Thirty three-six week old (weaning) rabbits were contribute in a 3 x 3 factorial used of completely randomized design having 3-5 individual replication and fed one out of three levels of lactosym (0, 0.25 and 0.50 ml/head/week). The two factors were: breed and level of lactosym. Result showed that there were no significant differences between breed (P>0,05) for body weight gain, feed intake and feed conversion. Body weight was affected by the level of lactosym (P<0,05). Increase of lactosym level decreased body weight gain. Feed conversion were not affected by the level of lactosym (P>0,05). Interaction between breed and level of lactosym did not affect body weight gain and feed conversion (P>0,05), but affected feed intake (P<0,05).   Key words: Productivity, rabbits, lactosym